Microsatellite loci for tucumã of Amazonas (Astrocaryum aculeatum) and amplification in other Arecaceae - Ramos, Santiago Linorio Ferreyra; Macedo, Jeferson Luis Vasconcelos de; Lopes, Maria Teresa Gomes; Batista, Jacqueline da Silva; Formiga, Kyara M.; Silva, Perla Pimentel da; Saulo-Machado, Antonio C.; Veasey, Elizabeth Ann (American Journal of Botany, 2012)
Premise of the study: Microsatellite loci were developed for tucumã of Amazonas (Astrocaryum aculeatum), and cross-species amplification was performed in six other Arecaceae, to investigate genetic diversity and population structure and to provide support for natural populations management. Methods and Results: Fourteen microsatellite loci were isolated from a microsatellite-enriched genomic library and used to characterize two wild populations of tucumã of Amazonas (Manaus and Manicoré cities). The investigated loci displayed high polymorphism for both A. aculeatum populations, with a mean observed heterozygosity of 0.498. Amplification rates ranging from 50% to 93% were found for four Astrocaryum species and two additional species of Arecaceae. Conclusions: The information derived from the microsatellite markers developed here provides significant gains in conserved allelic richness and supports the implementation of several molecular breeding strategies for the Amazonian tucumã. © 2012 Botanical Society of America.
Keywords: Microsatellite Dna; Dna, Plant; Primer Dna; Allele; Genetic Marker; Genetic Variation; Heterozygosity; Molecular Analysis; Monocotyledon; Polymorphism; Population Structure; Reproductive Strategy; Species Richness; Wild Population; Arecaceae; Dna Sequence; Polymorphism, Genetic; Genetics; Molecular Genetics; Nucleotide Sequence; Polymerase Chain Reaction; Arecaceae; Dna Primers; Dna, Plant; Microsatellite Repeats; Molecular Sequence Data; Polymerase Chain Reaction; Polymorphism, Genetic; Sequence Analysis, Dna; Amazonas; Amazonia; Manaus